Species trouble: reading Judith Butler's work through posthumanist spectacles - Husić, Snježana (2011)
The paper explores the relevance of Judith Butler’s model of gender performativity when applied to questions of species identity (human and non-human), with the aim to inquire whether her model can offer a feasible path or some useful insights for posthumanist theory and critical animal studies. The inquiry focuses chiefly on 'Gender Trouble' and on translatability of terms, categories and models proposed there: if gender is a work in progress of cultural construction with no unique original to cling to, species as well might not be a naturally given (id)entity ; instead, it might be just another performative that purports its own ‘naturalness’, in very much the same way a gender performative does it. From that point of view, Judith Butler’s model is compatible with Darwin’s idea of species as of a permanently changing and unstable category, and thus it appears to have great potential of translatability into both evolutionary and posthumanist terms. On the other hand, Butler’s use of certain categories such as nature/culture dichotomy in the first place, together with her conception of (human) subjectivity, might convey some preconceived contents – unintentional as they may be – which are often overlooked in the critique of her theorizing, and which are hardly consistent with a posthumanist stance. Therefore, the paper will also look into possibilities of creating a space for a non-human subject within Judith Butler’s theoretical framework.